SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM PENINGKATAN KINERJA GURU DI SDN KEDUNG COWEK 1 DAN SDS AL IKHLAS SURABAYA - Nurul Hamimah; Ainur Rifqi; Kaniati; Amrozi Khamidi; Banu Atmoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Academic supervision is one of the main competencies of school principals that plays an important role in improving teacher performance. This study aims to describe the planning, implementation, and follow-up of academic supervision by school principals and its impact on improving teacher performance at SDN Kedung Cowek 1 and SDS Al Ikhlas Surabaya. This study used a qualitative approach with a multi-site study type. Data collection techniques were carried out through observation, in-depth interviews, and documentation studies. The research subjects consisted of principals and teachers at both schools. Data analysis used the Miles and Huberman interactive model, which included data reduction, data presentation, and conclusion drawing. The results showed that academic supervision that was planned systematically, implemented collaboratively, and followed up through continuous guidance was able to improve teacher performance, particularly in the aspects of lesson planning, lesson implementation, and learning outcome evaluation. Effective academic supervision made teachers more professional, reflective, and innovative in the learning process.